Structural Changes and Growth in Kerala Economy - Santhosh Kumar S. AND Presteena Jesna M. Jose (Commerce Spectrum, 2014)
Economic reforms are primarily intended for achieving higher economic growth. It can make structural changes and shifts in economies over years. During 1990s Kerala wasahead of other states in the country except in the matter of industrialisation. The reforms introduced in the country has its own impact on the different sectors of the Kerala economy. The present paper examines the structural changes and growth of the State during the post- reform period in terms of 1) State Domestic Product and Per capita Income on absolute basis and 2)Sectoral Share of State Domestic Product in comparison to pre-reform period.It was foundthat the mean shares of the primary sector and the tertiary sector in Kerala during Phase I (1993-94 to 2002-03) and Phase II (2003-04 to 2013-13) in the post reform period differ significantly. However, the secondary sector remained stationary without reporting significant changes over the two phases. While the growth of the primary sector and secondary sectors were highly fluctuating, the growth of the tertiary sector was less fluctuating with consistent positive growth